IN VITRO ANTIBACTERIAL ACTIVITY OF ESSENTIAL PLANT OILS AGAINST BIOFILM FORMING METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - PUNITHA, THAMBIDURAI; MOORTHY, KANNAIYAN; VIJAYALAKSHMI, PONNUSAMY; VINODHINI, RAJA; SARANYA, SELVAM; BHUVANESHWARI, MURUGESAN; KANIMOZHI, CHINASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2014)
An alarming increase in biofilm forming methicillin-resistant Staphylococcus aureus (MRSA) possesses a serious problem in hospital environment demands a renewed effort to seek agents from natural system that are effective against pathogenic bacteria resistant to current antimicrobials. In the study, the distribution of biofilm forming MRSA and the antibacterial activity of essential oils (Eucalyptus, Mint, Turpentine, Neem and Amla) was studied in 58 strains of S. aureus isolated from pus samples. Out of 58 clinical samples 22 S. aureus were found to be methicillin-resistant and showed a dry black crystalline morphology indicating strong biofilm production and they were screened for the antibacterial activity of five different essential oils by using agar well diffusion method. The results from the agar well diffusion method showed that 4 essential oils could inhibit the growth of biofilm forming S. aureus isolates. Among those turpentine oil had strong inhibitory effects with a zone of inhibition ranging from 16.8 Â± 1.77 mm to 32.0 Â±2.12 mm. Eucalyptus oil shown moderate antibacterial activity against all tested isolates and followed by mint and neem with the average zones of inhibition. The oils at all concentrations showed potent inhibitory activity against the tested S. aureus with the exception of amla oil where there were no reports of inhibition. It is known that essential oils are composed of numerous different chemical compounds and their antimicrobial activity might be attributed to several different mechanisms, which could explain the variations in their mode of action. However, more studies are required to find the compounds of essential oils responsible for their antimicrobial activity, since little is known about essential oils and their medicinal property.